2018
DOI: 10.1186/s13063-018-2923-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity after Cardiac EventS (PACES) – a group education programme with subsequent text-message support designed to increase physical activity in individuals with diagnosed coronary heart disease: study protocol for a randomised controlled trial

Abstract: BackgroundCoronary heart disease (CHD) represents approximately 13% of deaths worldwide and is the leading cause of death in the UK with considerable associated health care costs. After a CHD event, timely cardiac rehabilitation optimises patient outcomes. However, a high percentage of these services do not meet necessary performance indicators such as course length and follow-up attendance. Uptake of such services is only 50% in UK patients and support provided 12 months after an event is often limited. To de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…al. [29] have reported that a high percentage of CVD patients—including patients with diabetes, cancer, and high blood pressure (BP)—do not achieve the recommended levels of PA. Zachariah et. al.…”
Section: Introductionmentioning
confidence: 99%
“…al. [29] have reported that a high percentage of CVD patients—including patients with diabetes, cancer, and high blood pressure (BP)—do not achieve the recommended levels of PA. Zachariah et. al.…”
Section: Introductionmentioning
confidence: 99%
“…A single-centre RCT with two parallel arms, the protocol has been previously described. 7 Participants Participants were recruited from the University Hospitals of Leicester National Health Service (NHS) Trust Cardiology Department and Phase Four community cardiac rehabilitation providers between March 2017 and March 2018 (recruitment target reached). Eligible participants were aged ≥18 years, 12-48 months after a CHD cardiac event diagnosis (myocardial infarction, angina, acute coronary syndrome (ACS)), had mobile phone access, willing to allow their general practitioner (GP) notification of study participation and medical records access (study purposes), willing to attend education sessions and able to speak and read English.…”
Section: Methodsmentioning
confidence: 99%
“…Passaglia et al (37) proposed that text messaging was effective in enhancing and controlling the risk factors in patients with ACS. Herring et al (38) confirmed the effect of SMS-based training on the physical activity of CHD patients. Also, in keeping with the present study, Safaie et al (39) suggested that texting could help promote adherence to treatment regimens among hypertensive patients.…”
Section: Discussionmentioning
confidence: 91%